Evaluation of circulating tumor cell clusters for pan‐cancer noninvasive diagnostic triaging. Issue 3 (30th September 2020) - Gaya, Andrew; Crook, Timothy; Plowman, Nicholas; Ranade, Anantbhushan; Limaye, Sewanti; Bhatt, Amit; Page, Raymond; Patil, Revati; Fulmali, Pradip; Datta, Vineet; Kumar, Prashant; Patil, Darshana; et al.
Abstract : Background: Histopathologic examination (HPE) of tumor tissue obtained by invasive biopsy is the standard for cancer diagnosis but is resource‐intensive and has been associated with procedural risks. The authors demonstrate that immunocytochemistry (ICC) profiling of circulating ensembles of tumor‐associated cells (C‐ETACs) can noninvasively provide diagnostic guidance in solid organ cancers. Methods: The clinical performance of this approach was tested on blood samples from 30, 060 individuals, including 9416 individuals with known cancer; 6725 symptomatic individuals with suspected cancer; and 13, 919 asymptomatic individuals with no prior diagnosis of cancer. C‐ETACs were harvested from peripheral blood and profiled by ICC for organ‐specific and subtype‐specific markers relevant to the cancer type. ICC profiles were compared with HPE diagnoses to determine concordance. Results: The presence of malignancy was confirmed by the detection of C‐ETACs in 91.8% of the 9416 individuals with previously known cancer. Of the 6725 symptomatic individuals, 6025 were diagnosed with cancer, and 700 were diagnosed with benign conditions; C‐ETACs were detected in 92.6% of samples from the 6025 individuals with cancer. In a subset of 3509 samples, ICC profiling of C‐ETACs for organ‐specific and subtype‐specific markers was concordant with HPE findings in 93.1% of cases. C‐ETACs were undetectable in 95% of samples from the 700 symptomatic individuals who had benign conditions and in 96.3% of samples from the 13, 919 asymptomatic individuals. Conclusions: C‐ETACs were ubiquitous (>90%) in various cancers and provided diagnostically relevant information in the majority (>90%) of cases. This is the first comprehensive report on the feasibility of ICC profiling of C‐ETACs to provide pan‐cancer diagnostic guidance with accuracy comparable to that of HPE. Abstract : Immunocytochemistry profiling of circulating ensembles of tumor‐associated cells conveys malignancy status as well as the organ of origin in several cancers, including brain cancer, with high sensitivity, specificity, and accuracy. This approach addresses the long‐unmet need for the noninvasive diagnostic triaging of symptomatic individuals with suspected cancers.